Population Genetic Analysis of Lobelia rhynchopetalum Hemsl. (Campanulaceae) Using DNA Sequences from ITS and Eight Chloroplast DNA Regions - Mulatu Geleta; Tomas Bryngelsson (The Scientific World Journal)
DNA sequence data from the internal transcribed spacer of nuclear ribosomal DNA and eight chloroplast DNA regions were used to investigate haplotypic variation and population genetic structure of the Afroalpine giant lobelia, Lobelia rhynchopetalum. The study was based on eight populations sampled from two mountain systems in Ethiopia. A total of 20 variable sites were obtained, which resulted in 13 unique haplotypes and an overall nucleotide diversity (ND) of 0.281 ± 0.15 and gene diversity (GD) of 0.85 ± 0.04. Analysis of molecular variance (AMOVA) revealed a highly significant variation (P<0.001) among populations (FST), and phylogenetic analysis revealed that populations from the two mountain systems formed their own distinct clade with >90% bootstrap support. Each population should be regarded as a significant unit for conservation of this species. The primers designed for this study can be applied to any Lobelia and other closely related species for population genetics and phylogenetic studies.